Influência do resíduo de minério de ferro na produção de painéis cimento-madeira - Narciso, Carolina Rezende Pinto (2018)
This paper aims to evaluate the effect of the use of the mining residue on the physical properties, mechanical, microstructural and thermal properties of cement-wood panels. The experimental design consisted of five treatments, being evaluated four percentages of substitution of Portland cement for the mining residue (0, 10, 20, 30 e 40%). Pinus oocarpa wood particles were evaluated on their anatomical, chemical and physical characteristics and the mining waste was evaluated on its granulometry and chemical composition. The panels were produced with a nominal density of 1.30 g / cm³; Wood ratio: cement of 1: 2.75; water: cement of 1.25; hydration rate (water): cement of 0,25, with Portland cement ARI CP-V and 2% calcium chloride (CaCl2) as an additive. The pressing cycle was 4MPa in the cold for ten minutes and after that time the panels were subjected to stapling for 24 hours and total cement cure of 28 days. The pinus wood and the mining residue were evaluated on their chemical composition, physical and dimensional properties. The physical, chemical, dimensional, cement reactions and index of inhibition of the materials and the physical, mechanical and thermal properties of the cement-wood panels were evaluated. As well as the accelerated aging of composites effect. The mining waste promoted inhibition of the cement cure, which directly affected the properties of cement-wood panels. The interaction between the main component of the mining tailings (SiO2) and the hydration phases of the cementitious matrix, acting as void fillers and contributing to the improvement of the physical properties of the composite was not observed. All treatments evaluated met the requirements of the marketing standard for MOR and MOE to static flexion and internal connection, even after accelerated aging. It is technically feasible to use 40% of mining residue for the production of cementwood panels on an industrial scale, a fact that may allow the aggregation of values and the adequate disposal of the mining residue.